Development of a Semirigid Pavement Incorporating Ultrarapid Hardening Cement and Chemical Admixtures for Cement Grouts - Jin Wook Bang; Byung Jae Lee; Yun Yong Kim (Advances in Materials Science and Engineering)
Mechanical tests were carried out to evaluate the influence and effects of fluidity and compressive strength of cement grout on semirigid asphalt pavement. An open graded asphalt skeleton was designed in order to achieve target porosity in the range of 18~22%. In addition, four types of cement grout mixtures were produced with varying mix proportions with ultrarapid hardening cement and chemical admixtures, that is, accelerating and retarding agents. For the semirigid pavement specimens, mechanical experiments to measure properties such as porosity, flexural strength, Marshall stability, and wheel tracking resistance were carried out. The test results demonstrated that the flow time (fluidity) of cement grout is the most significant factor that determines the mechanical properties of semirigid asphalt specimens under constant condition of the open graded asphalt skeleton. For the semirigid pavement mixing proportion in the current study, it is recommended that the porosity of the open graded asphalt skeleton and flow time of cement grout should be 20% and within 12 seconds, respectively.